New feather mites of the genus Amerodectes Valim and Hernandes (Acariformes: Proctophyllodidae) from passerines (Aves: Passeriformes) in Georgia, USA - Mironov, Sergey V.; Chandler, C. Ray (Zootaxa, 2017)
Eight new species of the feather mite genus Amerodectes Valim and Hernandes, 2010 (Proctophyllodidae: Pterodectinae) are described from passerines (Aves: Passeriformes) in Georgia, USA: Amerodectes cathari sp. n. from Catharus ustulatus (Nuttall) (Turdidae), A. haemorhous sp. n. from Haemorhous mexicanus (Muller, PLS) (Fringillidae), A. helmitheros sp. n. from Helmitheros vermivorum (Gmelin) (Parulidae), A. hribari sp. n. from Geothlypis trichas (Linnaeus) (Parulidae), A. hylocichlae sp. n. from Hylocichla mustelina (Gmelin) (Turdidae), A. passerinae sp. n. from Passerina ciris (Linnaeus) (Cardinalidae), A. seiurus sp. n. from Seiurus aurocapilla (Linnaeus) (Parulidae), and A. spizellae sp. n. from Spizella passerina (Bechstein) (Emberizidae). An updated world checklist of Amerodectes species and a key to species recorded and potentially expected in North America (USA and Canada) are proposed.